How does home government influence the internationalization of emerging market firms? The mediating role of strategic intents to internationalize - Angulo-Ruiz, Fernando; Pergelova, Albena; Wei, William Xiaojun (My University, 2019)
The purpose of this paper is to focus on the differential impact of government promotional measures and government ownership on two internationalization variables: location and speed of internationalization of emerging market multinationals (EMNEs). Central to the authors’ study is the mediating role of strategic intents to internationalize. In particular, we study how government impacts the resource-seeking, market-seeking and technology-seeking motives to internationalize. The empirical setting for the paper is Chinese companies that have internationalized via an equity based entry mode. The authors employ 672 firm responses collected by the Asia Pacific Foundation of Canada and the China Council for the Promotion of International Trade. The empirical results demonstrate that different home government measures have differential impact on internationalization outcomes. Government promotional measures (such as direct incentives and bilateral agreements to support internationalization) have only an indirect effect on international location and speed through the effect they have on the strategic motives to internationalize; while government ownership in the company has a direct impact on international location. The study highlights that home governments are shaping EMNEs strategic intent. Home government can influence EMNEs internationalization choices by providing resource flows through financial resources and state ownership or through asset-accumulation mechanisms via promotional measures .Policy makers in emerging markets need to develop policies focused on the specific motivations that firms have when internationalizing. EMNEs are suggested to take advantage of government policies more intentionally. The theoretical contribution centers on identifying important mediating mechanisms pointing to the interplay between government policies and international location and speed of firms. The authors contribute to the growing stream of research on internationalization of emerging market firms by building a sound theoretical model and examining empirically the role of home government in the internationalization of EMNEs.
Keywords: China; EMNEs; government measures; internationalization; emerging market; international trade; Canada